Implementation Of International Trade And Its Implications For Changes In National Business Views - Faizal Islam Akbar Alam; Nurul Asfiah (Jurnal Publikasi Ilmu Manajemen, 2024)
This research uses a bibliometric approach from international publication data accessed from the Google Scholar database which can be accessed via Harzing's Publish or Perish. Data collection was carried out by searching publications on Google Scholar regarding international trade and its coercion for responsible business with the keywords "international trade and its coercion for responsible business", with the category of article titles of 1000 journals and abstracts of 1000 journals. VosViewer software will be used to analyze the collected data. This software allows the creation and visualization of bibliometric maps displaying articles and other publications. The crucial role played by Social Enterprises (SE) in addressing social and environmental challenges. SE, as a hybrid organization connecting the volunteer and business sectors, becomes an important tool in helping organizations and developing strategies to achieve social goals. This article highlights the importance of understanding business models, with the Business Model Canvas (BMC) and Social Enterprise Model Canvas (SEMC) being effective tools in helping SEs develop strategies that are responsive to the challenges they face. With a multidimensional approach to mission values and objectives, as well as a deep understanding of stakeholders, SEMC is a strong instrument in facilitating sustainable growth and positive impact for SE. Through a holistic approach to business strategy and governance, SE can play a significant role in creating innovative solutions to social and environmental problems